Flow cytometry for assessing blood extracellular DNA fragments level in with post-COVID syndrome convalescent subjects - Kravtsov, Alexander L.; Klyueva, Svetlana N.; Kozhevnikov, Vitaly A.; Bugorkova, Svetlana A. (Infekt͡s︡ii͡a︡ i immunitet, 2025)
Patients with COVID-19 are characterized by markedly elevated levels of cell-free DNA in the peripheral blood, and recently neutrophil extracellular trap DNA strands were detected in the blood plasma of individuals with post-COVID syndrome. Purpose of the study — to develop a methodological approach (technology) for detecting cell-free DNA and to assess its level in the blood of individuals with post-COVID syndrome. Materials and methods. The study enrolled patients with post-COVID syndrome who had severe COVID-19 (experimental group, n = 8, aged 53 to 64 years); patients with severe COVID-19 (comparison group I, n = 5, aged 48 to 67 years); apparently healthy volunteers of different age groups: 18–30 years old (comparison group II, n = 12) and over 60 years old (comparison group III, n = 10, over 60 years old), in whose blood there were no specific IgG antibodies to the SARS-CoV-2 virus. The study was performed in microvolume whole blood samples. Results. To determine the content of intracellular DNA fragments in the blood, a flow cytofluorimetric analysis method was developed based on adding a propidium iodide dye solution to the blood together with the CD45-FITC marker used in leukocyte immunophenotyping according to the Lyse/No-Wash protocol to differentiate intact cells from cellular debris. In healthy subjects, after adding a reagent that lyses erythrocytes and fixes leukocytes to the blood, the dye penetrates into the cells and stains only the intracellular DNA in intact diploid leukocytes. The proportion of weak DNA fluorescence signals from extracellular DNA fragments in the total number of pulses recorded by the cytometer in this case not exceeds 3.2 (2.0–5.6)%. With age in case of the disease, this pattern increases to an average of 13.4 (10.1–18.6)%. In individuals with severe COVID-19, very high magnitude of the studied parameter was recorded — at the level of 82 (68.0–88.6)%. In COVID-19 convalescent patients, high levels of extracellular DNA remained for a month, gradually decreasing by the month 3 to 40.5 (27.4–52.0)%. Conclusion. According to the data obtained, the determination of extracellular DNA using the developed technology allows us to characterize the severity of COVID-19 and assess the compensatory capabilities of the body in the post-COVID period.